Comparative study of laser ignition and conventional electrical spark ignition systems in a hydrogen fuelled engine. (9th February 2015) - Pal, Anuj; Agarwal, Avinash Kumar
Abstract: Increasing population and demand for fossil fuels is leading to rapid depletion of petroleum reserves. Hydrogen has great promise as an alternative fuel for powering next generation internal combustion engines with improved thermal efficiency and reduced emissions. Laser ignition (LI) has emerged as an efficient ignition technique for delivering superior engine efficiency with lower emissions. Use of LI to initiate combustion in an engine fuelled with hydrogen–air mixtures can greatly help in reducing emissions, improving engine performance and tackling the problem of fossil fuel depletion. In this study, a laser ignited hydrogen fuel prototype engine has been developed and comparison of its performance, emissions and combustion parameters is done with baseline data generated using conventional spark ignition (SI) system. Highlights: Laser ignited (LI) hydrogen fuelled prototype engine was developed. Engine performance, emissions and combustion of LI is done with conventional SI. At all loads, Pmax, RoPR, HRR in case of LI were higher compared to SI. Combustion started earlier in LI and Combustion duration was shorter for LI. Engine performance parameters for LI were superior than SI.